Energy system contributions in indoor rock climbing - de Moraes Bertuzzi, Romulo Cassio; Franchini, Emerson; Kokubun, Eduardo [UNESP]; Peduti Dal Molin Kiss, Maria Augusta (Springer, 2007)
The present study cross-sectionally investigated the influence of training status, route difficulty and upper body aerobic and anaerobic performance of climbers on the energetics of indoor rock climbing. Six elite climbers (EC) and seven recreational climbers ( RC) were submitted to the following laboratory tests: ( a) anthropometry, (b) upper body aerobic power, and ( c) upper body Wingate test. on another occasion, EC subjects climbed an easy, a moderate, and a difficult route, whereas RC subjects climbed only the easy route. The fractions of the aerobic (WAER), anaerobic alactic (W-PCR) and anaerobic lactic (W-[La(])-) systems were calculated based on oxygen uptake, the fast component of excess post-exercise oxygen uptake, and changes in net blood lactate, respectively. on the easy route, the metabolic cost was significantly lower in EC [ 40.3 ( 6.5) kJ] than in RC [60.1 ( 8.8) kJ] ( P < 0.05). The respective contributions of the WAER, WPCR, and W-[La(])- systems in EC were: easy route = 41.5 (8.1), 41.1 (11.4) and 17.4% (5.4), moderate route = 45.8 (8.4), 34.6 (7.1) and 21.9% (6.3), and difficult route = 41.9 (7.4), 35.8 (6.7) and 22.3% (7.2). The contributions of the WAER, WPCR, and W-[La(])- systems in RC subjects climbing an easy route were 39.7 (5.0), 34.0 (5.8), and 26.3% (3.8), respectively. These results indicate that the main energy systems required during indoor rock climbing are the aerobic and anaerobic alactic systems. In addition, climbing economy seems to be more important for the performance of these athletes than improved energy metabolism.
Keywords: oxygen consumption; blood lactate; oxygen debt; energy sources; training status